PERAN ORANGTUA DALAM PENANAMAN TANGGUNGJAWAB PADA SISWA SD MUHAMMADIYAH AMBARKETAWANG 2 GAMPING - Nurmasita Nurmasita; Nurul Hidayati Rofiah (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
Based on the results of observations and interviews to classroom teachers conducted by researchers there are still students who are less focused in listening to the ongoing learning process, there are children who, when given an individual task by the teacher who then asked for answers to his friends, often students do the task no maximum and if given the task of the house did not complete. This research aims to Describe the role of parents in planting responsibilities, and describe the factors that support and hinder the cultivation of responsibility to students.The type of research is descriptive qualitative research type, with observation and interview data collection techniques while data analysis techniques using data reduction, presentation of data and conclusions and while the validity of the data used is triangulation techniques and triangulation of sources. The result of the research is the role of parents in the planting of responsibilities on the students of SD Muhammadiyah Ambarketawang 2 Gamping has implemented a good planting system in the form of motivation or support, meet the needs of children ranging from clothing, food and student boards, and be a mediator of children both in the scope of school and space the scope of the house and the contributing factors to the planting of responsibilities to the students is that there are some parents and who assume the character of responsibility is very important for the child by applying the punishment to the child if the child does not respond to the advice or motivation of the parents or teachers, and the assignment to the students is also applied by the teacher during the learning process takes place, and the inhibiting factor on planting the character of responsibility is the busyness of the working parents so that the time given to the child is slightly reduced